Cardiovascular Autonomic Neuropathy Contributes to Sleep Apnea in Young and Lean Type 1 Diabetes Mellitus Patients - Janovsky, Carolina Castro Porto Silva; Rolim, Luiz Clemente de Souza Pereira; Sá, João Roberto de; Poyares, Dalva; Tufik, Sergio; Silva, Ademir Baptista; Dib, Sergio Atala (Frontiers in Endocrinology, 2014)
Knowledge about association between sleep apnea and cardiovascular autonomic neuropathy (CAN) in type 1 diabetes mellitus (T1DM) might give some insight into the pathogenesis of this condition in these patients. In obese patients, excessive central adiposity, including a large neck circumference, can contribute to obstructive sleep apnea (OSA). Its presence in non-obese patients, however, indicates that it could be correlated with autonomic neuropathy. The aim of this study was to compare the prevalence of OSA in young and lean T1DM patients with and without CAN. We studied 20 adult, non-obese, T1DM patients who were divided into two groups according to the results of the cardiovascular autonomic reflex tests (CARTs). These two groups (9 with CAN and 11 without CAN) were compared to a control group of 22 healthy individuals, who were matched by age and BMI. A polysomnography was performed and sleep was analyzed. The CAN+ group had a significantly higher prevalence of sleep apnea compared to the other groups (67% CAN+; 23% CAN−; 4.5% controls: CAN+ vs. Control; p = 0.006 and CAN+ vs. CAN−; p = 0.02). The CAN− group had higher sleep efficiency compared to the CAN+ group, demonstrating impaired sleep architecture in diabetics with this chronic complication. In conclusion, OSA may be related to the presence of CAN in young and lean T1DM patients. It could contribute to worse the prognosis and reducing the quality of life of these patients without specific treatment of these conditions.